The relationship between transformational-transactional leadership styles on the employee performance in the construction sector, UAE - Ali, Alkhaaldi Saif Salem Saif (2022)
The objective of this study is to identify the relationship between transformational leadership-transactional leadership styles on employee performance in the construction sector of UAE. A quantitative research design was selected to answer two research questions and two hypotheses. Three set of instruements were used in the study which include; transformational, transactional and employee performance. Three hundred and thirty-one employees of cocntruction companies ere chosen using simple random sampling technique. Data analysis using the Pearson r correlation reflects a strong relationship between leadrship styles and employee peformance. The result showed that transformational leadership had positive relationship with employee performance with value of .827 and significant at p < .000. The finding also found that transactional leadership had significant relationship with employee performance with the value of .854 where p < .000. Further, this study found that leadership styles strongly associated with employees performance at construction companies in UAE. The implication of this study suggested that the employees of construction companies in UAE should be allow to seek for more professional training or skills in their fields that add to the quick realization of organizational goals and the top management need to give rewards that men are interested in because the majority who work in construction companies are male.